(untitled) (Research, Society and Development, 2022)
Introduction: Introduction: The population aging technological advances led to an increase in the number of elderly people with chronic and life-threatening diseases, requiring a demand for prepared and competent health professionals in palliative care. Objective: To systematically examine the literature on provision of education in palliative care for health professionals. Method: A systematic literature review was performed. Regarding the search for publications, it was carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature (LILACS) and International Literature in Health Sciences (PUBMED) databases. Results: 335 studies were found, 138 from Lilacs, 67 from Scielo and 130 from Pubmed, on which 09 publications met the criteria for inclusion in the study. Conclusion: From the analysis of the selected studies, it appears that there is a need to increase and improve the offers of educational programs in Palliative Care for health professionals, in which training still prioritizes programs aimed at treating acute and chronic clinical conditions of patients, without paying attention to the care that the patient should receive at the end of life, when there is no longer any disease-modifying therapy.